2009
DOI: 10.1103/physrevb.80.184302
|View full text |Cite
|
Sign up to set email alerts
|

Phonon density of states and heat capacity ofLa3xTe4

Abstract: The phonon density of states ͑DOS͒ of La 3−x Te 4 compounds ͑x = 0.0, 0.18, 0.32͒ was measured at 300, 520, and 780 K, using inelastic neutron scattering. A significant stiffening of the phonon DOS and a large broadening of features were observed upon introduction of vacancies on La sites ͑increasing x͒. Heat-capacity measurements were performed at temperatures 1.85Յ T Յ 1200 K and were analyzed to quantify the contributions of phonons and electrons. The Debye temperature and the electronic coefficient of heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
54
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 28 publications
10
54
1
Order By: Relevance
“…All of the measurements were carried out under vacuum in the temperature range of 300-750 K. Consistent measurements, within $10% for Seebeck and resistivity, were confirmed at NASA's Jet Propulsion Laboratory (JPL) (using W-Nb thermocouples) and at ZTPlus Inc. using the ULVAC-ZEM3 system on a sample with zT $1.4 at 700 K. Scanning Seebeck coefficient measurements (at 300 K) on the sample with Hall carrier density of 9 Â 10 19 cm À3 showed a Seebeck coefficient variation of only 5 mV K À1 (full width for 90% of the data). Heat capacity (C p ) is estimated by C p (k B per atom) ¼ 3.07 + 4.7 Â 10 À4 Â (T/K-300), which is obtained by fitting the experimental data reported by Blachnik and Igel 34 within an uncertainty of 2% for all the lead chalcogenides at T > 300 K. It should be emphasized that this simple equation agrees well with the theoretical prediction 35 taking the lattice vibration (Debye temperature 5 of 130 K), dilation (bulk modulus 36 of 39.8 GPa, the linear coefficient 5 of thermal expansion of 20 Â 10 À6 K À1 ) and charge carriers contributions into account. At 700 K or above this equation gives C p $10% higher than the Dulong-Petit value.…”
supporting
confidence: 69%
“…All of the measurements were carried out under vacuum in the temperature range of 300-750 K. Consistent measurements, within $10% for Seebeck and resistivity, were confirmed at NASA's Jet Propulsion Laboratory (JPL) (using W-Nb thermocouples) and at ZTPlus Inc. using the ULVAC-ZEM3 system on a sample with zT $1.4 at 700 K. Scanning Seebeck coefficient measurements (at 300 K) on the sample with Hall carrier density of 9 Â 10 19 cm À3 showed a Seebeck coefficient variation of only 5 mV K À1 (full width for 90% of the data). Heat capacity (C p ) is estimated by C p (k B per atom) ¼ 3.07 + 4.7 Â 10 À4 Â (T/K-300), which is obtained by fitting the experimental data reported by Blachnik and Igel 34 within an uncertainty of 2% for all the lead chalcogenides at T > 300 K. It should be emphasized that this simple equation agrees well with the theoretical prediction 35 taking the lattice vibration (Debye temperature 5 of 130 K), dilation (bulk modulus 36 of 39.8 GPa, the linear coefficient 5 of thermal expansion of 20 Â 10 À6 K À1 ) and charge carriers contributions into account. At 700 K or above this equation gives C p $10% higher than the Dulong-Petit value.…”
supporting
confidence: 69%
“…C ph, H and C D are contribution of harmonic phonons and lattice dilation, which can be calculated by sound velocity, thermal expansion coefficient, and density. [60] Normal and shear ultrasonic measurements were performed at room temperature using input from a Panametrics 5052 pulser/ receiver with the filter at 0.03 MHz. The response was recorded via a Tektronix TDS5054B-NV digital oscilloscope.…”
Section: Methodsmentioning
confidence: 99%
“…This thermal behavior was contrasted with high-pressure measurements, which showed that, at constant temperature, the phonons behave quasiharmonically upon compression 30 . Related effects of doping and temperature on the electronic structure and phonons in transition metals were reported in [45][46][47] .…”
Section: Introductionmentioning
confidence: 99%